2019
DOI: 10.1111/sjop.12571
|View full text |Cite
|
Sign up to set email alerts
|

Psychological characteristics in women football players: Skills, mental toughness, and anxiety

Abstract: Women's football has been far less studied than men's. This work's objectives were to: (1) analyze the differences in psychological skills, mental toughness (MT), and anxiety in women football players according to their level (national team, first division, and second division); and (2) predict those three levels (using a multivariate model) according to the players’ psychological skills, mental toughness, and anxiety. One hundred and forty‐two Icelandic women football players (23.5 ± 3.5 years) participated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 36 publications
2
33
4
1
Order By: Relevance
“…However, other studies, such as Bohórquez and Checa (2017), Sánchez et al (2012), andReche et al (2018), have shown different patterns than the present research, finding higher levels of A-S and RS in younger athletes and higher A-D and LOT-P in <16 years old. Kristjánsdóttir et al (2019) find no significant differences in futsal players in relation to competitive A-T or RS. These discrepancies between the different studies could be conditioned by the competitive level of the athletes (local-autonomous-nationalinternational), as these levels of competition can enhance and/or generate different responses in the variables analyzed.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…However, other studies, such as Bohórquez and Checa (2017), Sánchez et al (2012), andReche et al (2018), have shown different patterns than the present research, finding higher levels of A-S and RS in younger athletes and higher A-D and LOT-P in <16 years old. Kristjánsdóttir et al (2019) find no significant differences in futsal players in relation to competitive A-T or RS. These discrepancies between the different studies could be conditioned by the competitive level of the athletes (local-autonomous-nationalinternational), as these levels of competition can enhance and/or generate different responses in the variables analyzed.…”
Section: Discussioncontrasting
confidence: 66%
“…However, other studies, such as Bohórquez and Checa (2017), Sánchez et al (2012), and Reche et al (2018), have shown different patterns to the present research, which found higher levels of somatic anxiety and resilience in young people and greater deconcentration and pessimism in under-16s. Kristjánsdóttir et al (2019) found no significant differences in futsal players related to competitive anxiety or resilience. These results coincide with those presented by Reche-García et al (2020) where they do not find differences related to the age variables of the participants.…”
Section: Discussionmentioning
confidence: 60%
“…We consider the exclusion of gender differences of football players to be one of the limits of the presented study. We also base our assumptions on the study of Kristjánsdóttir et al (2019), which points out the importance of examining psychological skills and anxiety in female football players. For this reason, we recommend that future research also focus on gender differences in competitive anxiety, and guilt and shame proneness in the context of the Denollet personality in female football players and take into account possible differences in the psychological training of female athletes.…”
Section: Discussionmentioning
confidence: 99%
“…The present study applied sociodemographic questions in participants with the variables: gender, age, schooling level, club state, soccer experience, the average number of official games by month, experience in soccer (years), tournament experience, level of the championship ( Solleveld et al, 2015 ; Kristjánsdóttir et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%